2014
DOI: 10.1037/a0033547
|View full text |Cite
|
Sign up to set email alerts
|

Tracing children’s approaches to learning through Head Start, kindergarten, and first grade: Different pathways to different outcomes.

Abstract: This article reports on the study of differential change trajectories for early childhood approaches to leaming. A large sample (N = 2,152) of Head Start children was followed through prekindergarten, kindergarten, and first grade. Classroom learning behaviors were assessed by teachers through the Preschool Learning Behaviors Scale twice in Head Start and through the Leaming Behaviors Scale twice in both kindergarten and first grade. Item response theory was applied to form continuous scales of Competence Moti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 72 publications
(64 citation statements)
references
References 39 publications
(66 reference statements)
3
51
0
4
Order By: Relevance
“…With each dimension, McDermott et al. () conducted multiple‐group IRT vertically equating the PLBS and LBS aspects of Competence Motivation and Attentional Persistence. Each vertical scale featured 18 items and was calibrated using expected a posteriori (EAP) Bayesian (Thissen & Wainer, ) scaled scores ( SS s), where the reference group (prekindergarten) M = 50, SD = 10, and effective range = 1–99.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…With each dimension, McDermott et al. () conducted multiple‐group IRT vertically equating the PLBS and LBS aspects of Competence Motivation and Attentional Persistence. Each vertical scale featured 18 items and was calibrated using expected a posteriori (EAP) Bayesian (Thissen & Wainer, ) scaled scores ( SS s), where the reference group (prekindergarten) M = 50, SD = 10, and effective range = 1–99.…”
Section: Methodsmentioning
confidence: 99%
“…Each model held child age (in months) at entry to Head Start as a continuous covariate and other child covariates (child sex, ethnicity, provision of special needs services) as simultaneous binary explanatory variables in a multinomial logistic regression model using the general logit link function. Final models were constructed through a sequential series of pilot models examining collinearity, simple, interactive, and additive effects for smaller sets of covariates (as per Hosmer & Lemeshow, ) as guided to the extent possible by prior research (McDermott et al., , ). The objective was to ascertain the relative risk increment or reduction for latent growth class membership (estimated through the odds ratio) associated with each explanatory covariate.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to aspects of self-regulation such as reactivity, persistence and effortful control develop later, become more voluntary, and are shaped by caregivers throughout early childhood (Kochanska, Murray, & Harlan, 2000; Rothbart & Bates, 2006). Children at greater risk (e.g., from low-income families) show declines in persistence from preschool to first grade (McDermott, Rikoon, & Fantuzzo, 2014) and low levels of persistence from age 5 to 10 years (Zhou et al, 2007). Thus, a better understanding of what shapes the development of mastery motivation in early childhood could inform how parents and teachers optimally support the regulatory behaviors that underlie mastery motivation, particularly for children at greater risk.…”
Section: Introductionmentioning
confidence: 99%
“…Three such studies have been conducted by McDermott et al using longitudinally scaled measures of learning behaviors over the prekindergarten to early elementary period. McDermott et al identified longitudinal patterns of growth in learning behaviors from prekindergarten to first grade associated with distal academic and behavioral outcomes in a large sample of Head Start students (McDermott et al, ; McDermott, Rikoon, & Fantuzzo, ; McDermott, Rikoon, & Fantuzzo, ). Trajectories characterized by higher levels of learning behaviors were associated with second‐grade proficiency in reading, vocabulary, language, math, and science as well as more optimal classroom adjustment and attendance at the end of first grade.…”
Section: Importance For Learning and Developmentmentioning
confidence: 99%